Trends of Diabetes in Children and Adolescents in Pediatric Endocrinology Clinic and Clinical Pediatric Diabetes Center at Al Baha Central Hospital in Saudi Arabia - H. Alghamdi, Ahmed; N. Nasaif, Majida; , Ali S. Dammas; M Alghamdi, Jameel; A Alghamdi, Riyadh (Journal of Preventive Medicine And Care, 2016)
Objectives This study describes and compares the epidemiological criteria of children with diabetes from 2007 to 2014. Methods A prospective study conducted with 372 children with diabetes mellitus. An access program was used for data collection, and SPSS 17 was used to analyses the results. Results A total of 372 cases with diabetes were studied and were divided into three groups according age. The first age group was between one day and six years and comprised 128 (34.4%) patients. The second group aged 7- 12 years of age comprised 174 (46.7%) patients. The third group aged 13-18 years of age comprised 58 (15.59%) patients. The average age was 8.32 years. Females constituted 52 % (194 cases) of all cases. T1DM constituted 95.4%, equal to 355 patients, T2DM constituted 1.88%, equal to seven cases. Monogenic diabetes affected three patients or 0.79%, with one case of monogenic neonatal diabetes confirmed by genetic study, and two other cases suspected to be MODY. The highest incidence was observed in the autumn months, with 105 children affected, constituting 27.8 % cases. The year 2012 had the highest incidence rate, with 59 children and adolescents affected at an incidence rate of 25.48 / 100000.Al-Baha region had the highest number of cases constituting 37.7 % of cases. Diabetic ketoacidosis was the first presentation and constituted 44.2% of cases. Conclusion. Diabetes in children is increasing significantly in recent years, requiring more detailed analysis of its epidemiological factors to find out any significant correlations which may help in its prevention.
Keywords: Children with diabetes; diabetic ketoacidosis; polydipsia; T1DM; T2DM